Shoulder Dynamic Control Ratio and Rotation Range of Motion in Female Junior Elite Handball Players and Controls. Issue 2 (March 2018) - van Cingel, Robert; Habets, Bas; Willemsen, Linn; Staal, Bart
Abstract : Objective: To compare glenohumeral range of motion and shoulder rotator muscle strength in healthy female junior elite handball players and controls. Design: Cross-sectional case–control study. Setting: Sports medical center. Participants: Forty elite female handball players and 30 controls active in nonoverhead sports participated in this study. Main Outcome Measures: Passive external rotator (ER), internal rotator (IR), and total range of motion (TROM) of the dominant and nondominant arm were examined with a goniometer. An isokinetic dynamometer was used to evaluate concentric and eccentric rotator muscle strength at 60 and 120 degrees/s with dynamic control ratio (DCR = ERecc :IRcon ) as the main outcome parameter. Results: Except for the ER range of motion in the nondominant arm, no significant differences were found between groups for IR, ER of the dominant arm, and the TROM. Within the handball group, the side-to-side difference for IR of the dominant arm was −1.4 degrees. The ER and the TROM of the dominant arm were significantly larger, 6.3 and 4.9 degrees, respectively. For both groups, the DCR values were above 1 and no significant differences were found between the dominant and nondominant arm. The DCR values in the handball group were significantly lower than in the control group. Conclusions: Based on the adopted definitions for muscle imbalance, glenohumeral internal range of motion deficit and TROM deficit our elite female handball players seem not at risk for shoulder injuries. Prospective studies are needed to support the belief that a DCR below 1 places the shoulder at risk for injury.